A chicken intestinal ligated loop model to study the virulence of Clostridium perfringens isolates recovered from antibiotic-free chicken flocks. Issue 2 (4th March 2017) - Parent, Eric; Archambault, Marie; Charlebois, Audrey; Bernier-Lachance, Jocelyn; Boulianne, Martine
ABSTRACT: Necrotic enteritis (NE) is a major problem in antibiotic-free (ABF) chicken flocks and specific strains of Clostridium perfringens are known to induce NE. The objective of this study was to develop a chicken intestinal ligated loop model in order to compare the virulence of various C. perfringens strains recovered from consecutive ABF flocks with and without NE. Intestinal loops were surgically prepared in 10 anaesthetized specific-pathogen-free chickens and alternately inoculated with C. perfringens isolates or brain heart infusion (BHI) media. Histological lesion scoring was performed for each loop. All strains from NE-affected flocks induced histological lesions compatible with NE whereas inoculation of loops with a commensal C. perfringens strain or BHI did not. Among inoculated strains, CP0994 ( netB- positive and cpb2- positive) and CP-2003-1256 ( netB- positive) demonstrated mean histological lesion scores significantly higher ( P < 0.01) than those obtained with a commensal strain or BHI whereas strain CP1073 ( netB- negative and cpb2- positive) induced intestinal lesions without significantly higher scores. In loops where villi were colonized by Gram-positive rods, significantly higher ( P < 0.01) mean histological lesion scores were observed. This result supports the hypothesis that colonization of the intestinal mucosa by C. perfringens is a critical step in the pathogenesis of NE. Finally, we demonstrated the importance of controlling virulent C. perfringens strains in ABF chicken flocks as a highly virulent strain can be present in consecutive flocks with NE and possibly affect multiple flocks.